G-C3N4-porphyrin composite photocatalytic material as well as preparation method and application thereof

By compounding nanoscale g-C3N4 with copper salt and porphyrin molecules, g-C3N4-porphyrin composite photocatalytic material was prepared, which solved the shortcomings of the existing g-C3N4 materials in visible light utilization and photocatalytic antibacterial properties, and achieved the goal of achieving It has an efficient antibacterial effect under visible light.

CN119500273APending Publication Date: 2025-02-25FUJIAN NORMAL UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411649449.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The problems of the existing g-C3N4 photocatalytic materials in the rapid recombination of photogenerated electrons and hole pairs and the main absorption of ultraviolet light limit their utilization of visible light and photocatalytic antibacterial properties.

Method used

G-C3N4-porphyrin composite photocatalytic material was prepared by compositeing nanoscale g-C3N4 with copper salt and porphyrin molecules. The method includes mixing nanoscale g-C3N4 with a copper saline aqueous solution, performing a light reaction, and then heating and reacting with an alcohol solution of porphyrin to form a composite material.

Benefits of technology

Under visible light irradiation, g-C3N4-porphyrin composite photocatalytic material significantly improves its antibacterial properties and can achieve a 100% antibacterial rate within 20 minutes, which is better than the separate intermediate products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500273A_ABST
    Figure CN119500273A_ABST
Patent Text Reader

Abstract

The invention discloses a g-C3N4-porphyrin composite photocatalytic material as well as a preparation method and application thereof. The preparation method of the g-C3N4-porphyrin composite photocatalytic material comprises the following steps: 1) providing an aqueous dispersion of nanoscale g-C3N4; 2) mixing the aqueous dispersion of the nanoscale g-C3N4 with a copper salt aqueous solution; reacting the mixture under illumination with the wavelength lambda greater than or equal to 420 nm, and performing solid-liquid separation after the reaction is finished to obtain an intermediate product; 3) dispersing the intermediate product in alcohol to obtain an alcohol dispersion liquid of the intermediate product; the alcohol dispersion liquid of the intermediate product and an alcohol solution of porphyrin are subjected to a heating reaction, and the g-C3N4-porphyrin composite photocatalytic material is obtained. The composite photocatalytic material disclosed by the invention has relatively good photocatalytic antibacterial performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a g-C3N4-porphyrin composite photocatalytic material and a preparation method and application thereof. Background Art

[0002] Bacterial resistance is gradually becoming one of the most serious challenges facing global public health.

[0003] On the one hand, graphite-phase carbon nitride polymer (g-C3N4) has become a highly anticipated material due to its significant advantages in the field of photocatalytic antibacterial. g-C3N4 can efficiently produce reactive oxygen species (ROS) under light, which is the key to its antibacterial mechanism. Photoexcitation causes valence band electrons to transition to the conduction band, leaving holes, forming electron-hole pairs, and triggering chemical reactions to generate ROS. These ROS can destroy the cell walls and cell membranes of bacteria, causing leakage of cell contents, thereby killing the bacteria. Due to this physical destruction process, it is difficult for bacteria to develop resistance mechanisms, reducing the risk of drug resistance.

[0004] The facile and low-cost synthesis of g-C3N4 makes it very suitable for large-scale industrial production. g-C3N4 is easily surface-modified and compatible with a wide range of materials, which increases its potential for a variety of applications. The large specific surface area of ​​the material not only improves the contact efficiency with microorganisms, but also enhances the photocatalytic efficiency. Its unique electronic structure and stability ensure long-term effectiveness in different environments, while its good biocompatibility and low toxicity make it an ideal choice for biomedical applications.

[0005] However, pure g-C3N4 material has the problem of rapid recombination of photogenerated electrons and holes, and mainly absorbs ultraviolet light, which limits its utilization of visible light. In order to improve the light absorption efficiency, the researchers enhanced the transmission of photogenerated carriers by regulating the structure and morphology of g-C3N4, constructed heterostructures with other semiconductors to promote the effective separation and transfer of charges, and adjusted its electronic structure by ion doping, while broadening its absorption spectrum, so that it can more effectively utilize a wider solar spectrum including visible light, and improve its photocatalytic performance.

[0006] CN112375804A discloses an Au-g-C3N4 all-weather photocatalytic antibacterial material, and its preparation method steps are as follows: the first step is to put 4g of melamine powder into an alumina crucible, the second step is to put the crucible into a muffle furnace, set the program to raise the temperature to 550°C at a rate of 3°C / min, and calcine in an air atmosphere for 2 hours; the third step is to naturally cool the final product to room temperature and grind it into powder with a mortar to obtain a g-C3N4 nanomaterial; the fourth step is to redisperse the obtained g-C3N4 sample in 5mL of distilled water, then add chloroauric acid solution, stir and dry the suspension, put the obtained powder into a muffle furnace, and calcine at 550°C for 2 hours. This method requires the addition of Au, which is costly, and the photocatalytic antibacterial performance of the obtained product still needs to be improved.

[0007] CN116809108A ​​discloses a novel method for preparing a g-C3N4-ZnO composite photocatalytic material, comprising: weighing melamine and ZnO photocatalytic material in molar ratio, mixing them evenly, ultrasonicating, filtering, drying and roasting to obtain the g-C3N4 / ZnO composite photocatalytic material. The photocatalytic antibacterial performance of the product obtained by this method still needs to be improved.

[0008] CN117779152A discloses a method for preparing a photocatalytic nanocomposite coating, comprising: S1, dissolving an alkali metal salt and a soluble copper salt in a lactic acid aqueous solution, adjusting the pH of the mixed solution to acidity, and obtaining a soluble copper salt plating solution; S2, adding 2Dg-C3N4 to the soluble copper salt plating solution, mixing evenly, and using the electrolyte as an electrolyte; using a metal substrate as a working electrode, a copper sheet as a counter electrode, and a saturated calomel electrode as a reference electrode, and performing electrodeposition to obtain a photocatalytic nanocomposite coating. The method obtains a photocatalytic nanocomposite coating, the preparation method is complicated, and the photocatalytic antibacterial effect still needs to be improved.

[0009] On the other hand, porphyrin molecules have attracted much attention due to their good chromophore activity in the solar spectrum, large π-electron system, excellent electron-donating performance, strong UV-vis absorption ability and high O2-generation quantum yield. Porphyrin molecules also have structural modifiability and multiple coordination sites. However, their large π-electron conjugated system also easily leads to intermolecular aggregation, causing severe quenching of the excited state.

[0010] CN113383792A discloses a method for preparing a nano antibacterial agent of high-valent silver, zinc and copper composite, comprising the following steps: (1) preparing an aqueous solution of porphyrin derivatives with a concentration of 5-20 mmol / L, adding ammonia water, adjusting the pH to 7.5-8.0, and stirring for 1-2 hours until uniform; (2) adding 1.2-2 equivalents of silver nitrate, zinc nitrate and copper nitrate, and 0.5-1 equivalents of polyvinyl pyrrolidone to the solution based on the content of porphyrin derivatives, and refluxing at 80-100°C for 2-5 hours; (3) adding an appropriate amount of sodium carbonate to the solution, cooling the solution, centrifuging the solution, and collecting the supernatant; (4) freeze-drying the supernatant in a vacuum, dissolving it in an appropriate amount of hot ethanol, washing it, and filtering it, washing it repeatedly, and drying it at 60-80°C to obtain a nano antibacterial agent of high-valent silver, zinc and copper composite. The antibacterial effect of the antibacterial agent prepared by this method still needs to be improved.

[0011] CN118652258A discloses a method for preparing a porphyrin self-assembly material, comprising the following steps: mixing tetrakis(phenylsulfonic acid)porphyrin and an aqueous solution of a metal nitrate, and adjusting the pH value to 6.5-7.5 to obtain a mixed solution; then allowing the mixed solution to stand for more than 15 hours under light-proof conditions to obtain a porphyrin self-assembly material; wherein the metal ion in the metal nitrate is selected from Zn 2+ 、Bi 3+ , Ca 2+ , Pd 2+ , Fe 3+ 、Al 3+ 、Co 2+ 、Ag + 、Na + , Gd 2+ and Cu 2+ The method mainly involves the reaction of tetrakis(phenylsulfonate)porphyrin with metal ion Zn 2+ 、Bi 3+ , Ca 2+ The antibacterial effect of the obtained product still needs to be improved.

[0012] So far, no results have been found to 2+ , reports on the formation of photocatalytic antibacterial materials by porphyrin molecular complexes. Summary of the invention

[0013] In view of this, an object of the present invention is to provide a method for preparing a g-C3N4-porphyrin composite photocatalytic material, wherein the g-C3N4-porphyrin composite photocatalytic material obtained by the preparation method has good antibacterial properties under visible light irradiation.

[0014] Another object of the present invention is to provide a g-C3N4-porphyrin composite photocatalytic material prepared according to the preparation method as described above.

[0015] Another object of the present invention is to provide the use of the g-C3N4-porphyrin composite photocatalytic material as described above in the preparation of photocatalytic antibacterial materials.

[0016] The present invention adopts the following technical solutions to achieve the above-mentioned purpose.

[0017] In one aspect, the present invention provides a method for preparing a g-C3N4-porphyrin composite photocatalytic material, comprising the following steps:

[0018] 1) Providing an aqueous dispersion of nano-scale g-C3N4;

[0019] 2) mixing an aqueous dispersion of nano-scale g-C3N4 with an aqueous solution of a copper salt to obtain a mixture; reacting the mixture under light with a wavelength λ greater than or equal to 420 nm, and separating the solid and the liquid after the reaction is completed to obtain an intermediate product;

[0020] 3) dispersing the intermediate product in alcohol to obtain an alcohol dispersion of the intermediate product; heating the alcohol dispersion of the intermediate product and an alcohol solution of porphyrin to react to obtain a g-C3N4-porphyrin composite photocatalytic material.

[0021] According to the preparation method of the present invention, preferably, in step 1), the concentration of the aqueous dispersion of nano-scale g-C3N4 is 0.5-5 mg / mL.

[0022] According to the preparation method of the present invention, preferably:

[0023] In step 2), the concentration of the copper salt aqueous solution is 4 to 20 mmol / L, and the copper salt in the copper salt aqueous solution is selected from one of copper chloride, copper sulfate, copper nitrate and copper acetate;

[0024] In step 2), the nano-g-C3N4 in the aqueous dispersion of nano-g-C3N4 and the Cu in the copper salt aqueous solution 2+ The dosage ratio is 25mg:0.03~0.1mmol.

[0025] According to the preparation method of the present invention, preferably:

[0026] In step 2), a water dispersion of nano-scale g-C3N4 is mixed with a copper salt aqueous solution, and air in the system is removed to obtain a mixture; the mixture is reacted under the light of a 300-400W Xe lamp, and a UV cutoff filter is installed on the Xe lamp to intercept light with a wavelength λ less than 420nm;

[0027] In step 2), the solid obtained by solid-liquid separation is washed and dried to obtain an intermediate product.

[0028] According to the preparation method of the present invention, preferably, in step 3), the concentration of the alcohol dispersion of the intermediate product is 0.3-5 mg / mL; the concentration of the alcohol solution of the porphyrin is 0.03-5 mmol / L; the volume ratio of the alcohol dispersion of the intermediate product to the alcohol solution of the porphyrin is 1-2:1; and the alcohol is selected from at least one of methanol, ethanol and isopropanol.

[0029] According to the preparation method of the present invention, preferably:

[0030] In step 3), the alcohol dispersion of the intermediate product and the alcohol solution of porphyrin are reacted under reflux conditions for 6 to 18 hours; after the reaction is completed, the solvent is removed and dried to obtain a g-C3N4-porphyrin composite photocatalytic material;

[0031] In step 3), the porphyrin is tetrakis(4-carboxyphenyl)porphine.

[0032] According to the preparation method of the present invention, preferably, the nanoscale g-C3N4 is prepared by the following steps:

[0033] (a) calcining urea or melamine, grinding, and obtaining a grinding product;

[0034] (b) dispersing the ground product in water and subjecting it to ultrasonic treatment to obtain a mixed solution;

[0035] (c) The mixed solution is centrifuged at a speed of 2500-4500 rpm to obtain an upper dispersion; the upper dispersion is then centrifuged again at a speed of 7000-12000 rpm, the precipitate is dried to obtain nano-scale g-C3N4.

[0036] According to the preparation method of the present invention, preferably, the calcination temperature is 500-700° C., and the calcination time is 1.5-4 h.

[0037] On the other hand, the present invention also provides a g-C3N4-porphyrin composite photocatalytic material, which is prepared according to the preparation method described above.

[0038] On the other hand, the present invention also provides a use of a g-C3N4-porphyrin composite photocatalytic material prepared according to the preparation method as described above in the preparation of a photocatalytic antibacterial material.

[0039] The g-C3N4-porphyrin composite photocatalytic material obtained by the present invention shows excellent antibacterial performance in the photocatalytic antibacterial experiment, especially under visible light conditions, and can reach a 100% antibacterial rate within 20 minutes. The g-C3N4-porphyrin composite photocatalytic material obtained by the preparation method of the present invention is presumed to be a composite material with a bridge-pillared structure, in which the Cu nanoparticles (abbreviated as Cu NPs) serve as an effective interface connector to enhance the interaction between g-C3N4 and porphyrin. The g-C3N4-porphyrin composite photocatalytic material of the present invention and the preparation method thereof provide a new research direction for the field of photocatalytic antibacterial. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 XRD patterns of the ground products CN-Bulk and CN-NS of Preparation Example 1, CN-TCPP-Cu of Example 1, CN-TCPP of Comparative Example 1, and CN-TCPP / Cu of Comparative Example 2 are shown.

[0041] Figure 2 The UV diffuse reflectance spectra of the calcined unground product CN-Bulk and the product CN-NS of Preparation Example 1, the product CN-TCPP-Cu of Example 1, the product CN-TCPP of Comparative Example 1, and the product CN-TCPP / Cu of Comparative Example 2 are shown.

[0042] Figure 3-1 The SEM results of the product CN-NS of Preparation Example 1 and the product CN-TCPP-Cu of Example 1 are shown. Among them, Figure a is the SEM image of CN-NS, and Figure b is the SEM image of CN-TCPP-Cu.

[0043] Figure 3-2 The TEM results of TCPP, the product CN-NS of Preparation Example 1, the product CN-TCPP of Comparative Example 1, and the product CN-TCPP-Cu of Example 1 are shown. Among them, Figure c is the TEM result of CN-NS, Figure d is the TEM result of TCPP, Figure e is the TEM result of CN-TCPP, and Figure f is the TEM result of CN-TCPP-Cu.

[0044] Figure 3-3 The results of energy dispersive X-ray spectroscopy (EDS) mapping and X-ray photoelectron spectroscopy (XPS) of the product CN-TCPP-Cu of Example 1 are shown. Among them, Figure i is the EDS mapping diagram of CN-TCPP-Cu.

[0045] Figure 4 The XPS full spectrum results of the product CN-TCPP-Cu of Example 1 are shown.

[0046] Figure 5The antibacterial test results of the product CN-TCPP-Cu and the intermediate product CN-Cu of Example 1 under visible light conditions are shown.

[0047] Figure 6 The antibacterial test results of the product CN-TCPP-Cu and the intermediate product CN-Cu of Example 1 under dark conditions are shown.

[0048] Figure 7 The antibacterial test results of the product CN-TCPP / Cu of Comparative Example 2 and the product CN-TCPP of Comparative Example 1 under visible light and dark conditions are shown respectively.

[0049] Figure 8 The fluorescence spectrum results of the product CN-TCPP-Cu of Example 1 are shown. Figure a is the fluorescence intensity spectrum at different times at the same concentration, Figure b is the fluorescence intensity comparison between the blank group and the composite photocatalytic material group at 20 minutes, and Figure c is the fluorescence intensity comparison between the blank group and the composite photocatalytic material group at 50 minutes.

[0050] FIG9( a ) and FIG9 ( b ) respectively show the hemolytic test results and cytotoxicity test results of the product CN-TCPP-Cu of Example 1. DETAILED DESCRIPTION

[0051] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0052] The inventors of the present application have discovered through in-depth research and multiple experiments that a g-C3N4-porphyrin composite photocatalytic material having a specific composition and structure formed by a specific method has better photocatalytic antibacterial properties, thereby completing the present invention.

[0053] <Preparation method>

[0054] The present invention provides a method for preparing a g-C3N4-porphyrin composite photocatalytic material, comprising the following steps: 1) providing a water dispersion of nano-scale g-C3N4; 2) obtaining an intermediate product; 3) obtaining a g-C3N4-porphyrin composite photocatalytic material. Optionally, the method further comprises a step of preparing nano-scale g-C3N4. The method is described in detail below.

[0055] Preparation steps of nano-scale g-C3N4

[0056] In the present invention, the preparation of nano-scale g-C3N4 is not particularly limited, and a method known in the art can be used. Preferably, a preparation method of g-C3N4 that can obtain nanosheets is used.

[0057] According to one embodiment of the present invention, the preparation method of the nano-scale g-C3N4 comprises the following steps: (a) calcining and grinding the raw material to obtain a grinding product; (b) dispersing the grinding product in water and ultrasonically treating it to obtain a mixed solution; (c) centrifuging the mixed solution at a speed of 2500 to 4500 rpm to obtain an upper dispersion; then centrifuging the upper dispersion at a speed of 7000 to 12000 rpm, taking the precipitate and drying it to obtain nano-scale g-C3N4. The obtained nano-scale g-C3N4 is a nanosheet.

[0058] In step (a), the raw material for calcination may be urea and / or melamine, preferably urea. The calcination temperature may be 500-700° C., preferably 520-650° C., more preferably 550-600° C. The calcination time may be 1.5-4 h, preferably 2-4 h, more preferably 2-3 h.

[0059] The heating rate during calcination can be 3.5-8°C / min, preferably 4-7°C / min, and more preferably 4.5-6°C / min. This is conducive to obtaining nano-scale g-C3N4 with higher purity.

[0060] The grinding may be performed by known methods, for example, grinding may be performed using a mortar.

[0061] In step (b), the mass volume ratio of the ground product to water can be 0.1 g: 15-40 mL, preferably 0.1 g: 17-30 mL, and more preferably 0.1 g: 20-25 mL. The power during ultrasonic treatment can be 50-250 W, preferably 80-200 W, and more preferably 100-150 W. The ultrasonic treatment time can be 8-20 h, preferably 10-18 h, and more preferably 12-15 h. This is conducive to uniform and thorough dispersion.

[0062] In step (c), the mixed solution can be centrifuged at a speed of 2500 to 4500 rpm, preferably at a speed of 2800 to 4000 rpm, more preferably at 3000 to 3500 rpm. Then the upper dispersion is taken and centrifuged at a speed of 7000 to 12000 rpm, preferably at a speed of 7500 to 10000 rpm, more preferably at 8000 to 10000 rpm, and then the precipitate is dried to obtain nano-scale g-C3N4. This is conducive to obtaining nano-sheet g-C3N4 with higher purity.

[0063] Step of providing an aqueous dispersion of nano-sized g-C3N4

[0064] The nanosheet g-C3N4 obtained as above is dispersed in water to obtain an aqueous dispersion of nano-scale g-C3N4. The concentration of the aqueous dispersion of nano-scale g-C3N4 is 0.5 to 5 mg / mL, preferably 0.8 to 2.5 mg / mL, and more preferably 1.0 to 2.0 mg / mL. According to a specific embodiment of the present invention, the concentration of the aqueous dispersion of nano-scale g-C3N4 is 1.0 to 1.2 mg / mL.

[0065] In this step, ultrasonic treatment can be used for dispersion, which is conducive to obtaining a more uniformly dispersed aqueous dispersion of nano-scale g-C3N4.

[0066] Steps to obtain intermediate products

[0067] The aqueous dispersion of nano-scale g-C3N4 is mixed with an aqueous solution of a copper salt to obtain a mixture; the mixture is reacted under light with a wavelength λ greater than or equal to 420nm, and after the reaction is completed, the solid and liquid are separated to obtain an intermediate product. The intermediate product can be recorded as CN-Cu.

[0068] According to one embodiment of the present invention, a nano-scale g-C3N4 aqueous dispersion is mixed with a copper salt aqueous solution, and air in the system is removed to obtain a mixture; the mixture is reacted under light with a wavelength λ greater than or equal to 420nm, and after the reaction is completed, the solid and liquid are separated to obtain an intermediate product. This is conducive to obtaining a g-C3N4-porphyrin composite photocatalytic material with better photocatalytic antibacterial performance.

[0069] In the present invention, the concentration of the copper salt aqueous solution can be 4 to 20 mmol / L, preferably 6 to 15 mmol / L, and more preferably 9 to 12 mmol / L. The copper salt in the copper salt aqueous solution is selected from one of copper chloride, copper sulfate, copper nitrate and copper acetate, preferably copper chloride. The copper salt used to prepare the copper salt aqueous solution may contain crystal water or may not contain crystal water. According to a specific embodiment of the present invention, the copper salt is selected from one of copper chloride dihydrate, copper sulfate pentahydrate, copper nitrate trihydrate and copper acetate monohydrate, preferably copper chloride dihydrate.

[0070] In the present invention, the nano-g-C3N4 in the aqueous dispersion of nano-g-C3N4 and the Cu in the copper salt aqueous solution 2+ The dosage ratio is 25 mg: 0.03-0.1 mmol, preferably 25 mg: 0.04-0.08 mmol, and more preferably 25 mg: 0.04-0.06 mmol.

[0071] In the present invention, after the aqueous dispersion of nano-scale g-C3N4 is mixed with the copper salt aqueous solution, the air in the system is removed. This is conducive to removing oxygen in the reaction bottle and the solvent, thereby facilitating the separation of nano-scale g-C3N4 and Cu 2+reaction.

[0072] According to a specific embodiment of the present invention, the specific steps of removing air from the system include: sealing the reaction bottle, freezing the mixture with liquid nitrogen, evacuating the reaction bottle, thawing the mixture, and then freezing it with liquid nitrogen again and evacuating the mixture, undergoing a total of three freezing-vacuuming-thawing processes to remove the air from the reaction bottle and the mixture.

[0073] In the present invention, the mixture can be reacted under light with a wavelength λ greater than or equal to 420nm. In certain specific embodiments, the mixture can be stirred and reacted for 1.5 to 4.5 hours under the light irradiation of a 300 to 400W Xe lamp equipped with an ultraviolet cutoff filter that intercepts light with a wavelength λ less than 420nm. The reaction time is preferably 2 to 4 hours, and more preferably 2 to 3 hours. After the reaction is completed, the solid and liquid are separated, and the separated solid is washed with ethanol, and the washed solid is dried to obtain an intermediate product. The drying can be vacuum drying, and the drying temperature can be 45 to 70°C, preferably 55 to 70°C, and more preferably 55 to 60°C.

[0074] Steps for obtaining g-C3N4-porphyrin composite photocatalytic materials

[0075] In the present invention, the intermediate product is dispersed in alcohol to obtain an alcohol dispersion of the intermediate product; the alcohol dispersion of the intermediate product and an alcohol solution of porphyrin are heated to react to obtain a g-C3N4-porphyrin composite photocatalytic material.

[0076] In the present invention, the concentration of the alcohol dispersion of the intermediate product can be 0.3-5 mg / mL, preferably 0.6-2.5 mg / mL, and more preferably 1.0-1.5 mg / mL. The concentration of the alcohol solution of the porphyrin can be 0.03-5 mmol / L, preferably 0.05-2.5 mmol / L, more preferably 0.06-1 mmol / L, and more preferably 0.06-0.1 mmol / L. The volume ratio of the alcohol dispersion of the intermediate product to the alcohol solution of the porphyrin can be 1-2:1, preferably 1.1-1.8:1, and more preferably 1.2-1.5:1. This is conducive to obtaining a composite material product with better photocatalytic antibacterial properties.

[0077] According to a specific embodiment of the present invention, the porphyrin may be tetrakis(4-carboxyphenyl)porphine. In the present invention, the alcohol is selected from at least one of methanol, ethanol and isopropanol, preferably ethanol.

[0078] In the present invention, the heating reaction is a reflux reaction, and the reaction time may be 6 to 18 hours, preferably 8 to 16 hours, and more preferably 10 to 15 hours.

[0079] After the heating reaction is completed, the solvent can be directly removed by concentration without solid-liquid separation, and the concentrate can be dried without washing to obtain a g-C3N4-porphyrin composite photocatalytic material, which is recorded as CN-TCPP-Cu. The drying can be vacuum drying, and the drying temperature can be 45 to 70°C, preferably 55 to 70°C, and more preferably 55 to 60°C.

[0080] <Composite photocatalytic materials and applications>

[0081] The present invention provides a g-C3N4-porphyrin composite photocatalytic material prepared according to the preparation method as described above. The present invention also provides the use of the prepared g-C3N4-porphyrin composite photocatalytic material in the preparation of a photocatalytic antibacterial material. The composite photocatalytic material has good photocatalytic antibacterial performance. In the present invention, CN-TCPP-Cu exhibits excellent antibacterial performance under visible light conditions, and can achieve a 100% inhibition rate on E. coli within 20 minutes, while the intermediate product CN-Cu requires 50 minutes to achieve substantially the same effect.

[0082] <Test Method>

[0083] XRD was measured using a Rigaku Miniflex 600 X-ray diffractometer.

[0084] Energy dispersive X-ray spectroscopy (EDS) was measured using an Xflash 6T / 60 X-ray spectrometer from Bruker, Germany.

[0085] SEM was measured using a Phenomenon LE scanning electron microscope from Phenom, the Netherlands.

[0086] TEM was measured using a Talos F200i transmission electron microscope from Thermo Fisher, USA.

[0087] The UV diffuse reflectance spectrum was measured using an Agilent Cary 7000 UV-visible-near-infrared spectrophotometer.

[0088] The fluorescence spectra were measured using an FS5 steady-state transient fluorescence spectrometer from Edinburgh Instruments, UK.

[0089] Preparation Example 1-Preparation of Nanoscale g-C3N4

[0090] 10 g of urea was ground and placed in a crucible, and then the crucible containing urea was placed in a muffle furnace, heated to 550° C. at a heating rate of 4.6° C. / min, and calcined at 550° C. for 2 h. The temperature was naturally lowered, and the sample (the sample was recorded as CN-Bulk) was taken out and ground to obtain a ground product.

[0091] 0.3 g of the ground product was dispersed in 60 mL of deionized water and ultrasonically treated at 100 W for 12 h to obtain a mixed solution.

[0092] The mixed solution was centrifuged at 3000 rpm to remove the blocky g-C3N4 that was not completely peeled off, and the upper dispersion was retained. The upper dispersion was centrifuged at 8000 rpm, and the precipitate was dried at 70°C to obtain nano-scale g-C3N4, which is a nanosheet. It is denoted as CN-NS.

[0093] Example 1

[0094] 25 mg of nano-scale g-C3N4 (CN-NS) prepared in Preparation Example 1 was placed in a Schlenk bottle, 20 mL of water was added, and ultrasonic treatment was performed to obtain an aqueous dispersion of nano-scale g-C3N4.

[0095] 4.5 mL of a 9.1 mmol / L copper salt aqueous solution (prepared from copper chloride containing two crystal waters) was added dropwise to the aqueous dispersion of nano-scale g-C3N4, stirred at room temperature for 30 min, and the air in the system was removed by repeating the freezing-vacuuming-thawing process three times to obtain a mixture. The mixture was then stirred and reacted for 2 h under the irradiation of a 300 W Xe lamp (equipped with an ultraviolet cutoff filter to intercept light with a wavelength of less than 420 nm). After the reaction was completed, the mixture was filtered, the solid was washed with ethanol, and the washed solid was vacuum dried at 60 ° C to obtain an intermediate product, which was recorded as CN-Cu.

[0096] The specific steps of removing the air from the system include: sealing the Schlenk bottle, freezing the mixture with liquid nitrogen, evacuating the double-row tube, thawing the mixture, and then freezing it with liquid nitrogen again and evacuating the mixture, a total of three freezing-vacuuming-thawing processes are performed to remove the air from the reaction bottle and the mixture.

[0097] 25 mg of the intermediate product (CN-Cu) was dispersed in 25 mL of ethanol by ultrasonic treatment to obtain an alcohol dispersion of the intermediate product. Under stirring, 20 mL of an alcohol solution of porphyrin with a concentration of 0.063 mmol / L (formed by dissolving tetrakis(4-carboxyphenyl)porphine in ethanol) was added to the alcohol dispersion of the intermediate product, and refluxed at 60°C for 12 hours. After the reaction was completed, the solvent was concentrated and the concentrate was vacuum dried at 60°C to obtain a g-C3N4-porphyrin composite photocatalytic material. It was recorded as CN-TCPP-Cu.

[0098] Comparative Example 1

[0099] 25 mg of nano-scale g-C3N4 (CN-NS) prepared in Preparation Example 1 was dispersed in 25 mL of anhydrous ethanol by ultrasonic treatment to obtain an alcohol dispersion of nano-scale g-C3N4. Then, 10 mL of an alcohol solution of porphyrin (formed by dissolving tetrakis(4-carboxyphenyl)porphine in ethanol) (1 mg / 10 mL, i.e., 10 mL of an alcohol solution of porphyrin contained 1 mg of porphyrin) was added to the alcohol dispersion of the intermediate product, ultrasonicated for 1 h, and then refluxed at 60° C. for 12 h. After the reaction was completed, the solvent was removed by concentration, and the concentrate was vacuum dried at 60° C. The obtained product was recorded as CN-TCPP, which did not contain Cu element.

[0100] Comparative Example 2

[0101] The order of adding materials in this comparative example is different from that in Example 1, and the specific preparation steps are as follows:

[0102] First, Cu 2+ Steps for coordination with porphyrin N: 25 mg of tetrakis(4-carboxyphenyl)porphine (TCPP) and cupric chloride dihydrate (the molar ratio of the two is 1:1) are placed in 15 mL of DMF respectively, and the two dissolved solutions are fully dissolved by ultrasound. The two dissolved solutions are then mixed and poured into a polytetrafluoroethylene-lined reactor, and reacted at 150° C. for 12 hours. The mixture is naturally cooled to room temperature, the solvent is removed by concentration, and the concentrate is dried. The intermediate product obtained is recorded as TCPP / Cu.

[0103] Steps of reacting with nano-scale g-C3N4: ultrasonically disperse 25 mg of g-C3N4 nanosheets (CN-NS) prepared in Preparation Example 1 in 25 mL of anhydrous ethanol, then add the prepared TCPP / Cu ethanol solution (1.1 mg / 10 mL, i.e., 10 mL of ethanol solution contains 1.1 mg of TCPP / Cu), and continue ultrasonication for 1 hour. Then, reflux the reaction system at 60°C for 12 hours, remove the solvent by concentration, and vacuum dry the concentrate at 60°C. The obtained product is recorded as CN-TCPP / Cu.

[0104] Experimental example

[0105] 1. Characterization by spectral analysis

[0106] XRD analysis was performed on CN-Bulk and CN-NS obtained in Preparation Example 1, CN-TCPP-Cu obtained in Example 1, CN-TCPP obtained in Comparative Example 1, and CN-TCPP / Cu obtained in Comparative Example 2. The results are shown in Table 1. Figure 1 ; UV diffuse reflectance spectroscopy analysis was performed, and the results are shown in Figure 2 .

[0107] The CN-NS prepared in Example 1 and the CN-TCPP-Cu obtained in Example 1 were subjected to SEM analysis. Figure 3-1 From the SEM image, it can be seen that CN-TCPP-Cu presents a lamellar structure, and after the introduction of TCPP, its thickness increases compared with the original CN-NS.

[0108] The CN-NS of Preparation Example 1, the CN-TCPP obtained in Comparative Example 1, and the CN-TCPP-Cu obtained in Example 1 were subjected to TEM analysis. The results are shown in FIG. Figure 3-2 The results of energy dispersive X-ray spectroscopy (EDS) mapping and X-ray photoelectron spectroscopy (XPS) of CN-TCPP-Cu obtained in Example 1 are shown in Figure 3-3 From the TEM images, we can see that CN-NS is a small-sized flake with more curled edges, while TCPP molecules are in a state of irregular aggregation (see Figure 3-2 When CN and TCPP are combined, a lamellar porous structure is formed on the surface of CN-NS due to the aggregation of TCPP molecules in the plane (see Figure 3-2 In CN-TCPP-Cu, this porous structure is reduced, indicating that the binding mode of TCPP molecules to CN-NS has changed and most TCPP molecules no longer exist in the form of aggregates (see Figure 3-2 In addition, the thickness of CN-TCPP-Cu increases, indicating the formation of a multilayer structure, and the edge curling phenomenon decreases, which should suggest that TCPP may be combined with CN-NS in a bridging pillaring manner rather than a simple π-π stacking.

[0109] It is worth noting that no lattice fringes of Cu element were observed under high magnification TEM images, which confirms the high dispersion of Cu nanoparticles (Cu-NPs) in the material, which is consistent with the conclusion of XRD speculation. Energy dispersive X-ray spectroscopy (EDS) mapping images further show the uniform distribution of C, N, and Cu elements in CN-TCPP-Cu materials, as well as the presence of a small amount of O element, which may come from the carboxyl group in the TCPP molecule and partially oxidized Cu (see Figure 3-3 These results indicate that the present invention has successfully prepared a CN-TCPP-Cu composite material with a specific morphology and structure.

[0110] The XPS full spectrum results of CN-TCPP-Cu obtained in Example 1 are shown in Figure 4Although the X-ray diffraction (XRD) and transmission electron microscopy (TEM) analysis failed to directly observe the presence of copper (Cu) element, the results of energy dispersive X-ray spectroscopy (EDS) mapping and X-ray photoelectron spectroscopy (XPS) confirmed that the Cu element does exist in the material.

[0111] The present invention also found that from CN-Cu to CN-TCPP-Cu, the binding energy peak of Cu moves to a higher energy. This indicates that after CN-Cu is compounded with TCPP, the electron density of Cu decreases, and the electrons generated by the TCPP molecule are not transferred to the Cu element. The present invention believes that this phenomenon indicates that Cu is not combined with the nitrogen (N) atom of the porphyrin, but exists in an independent form outside the porphyrin molecule.

[0112] The present invention found that after complexing with TCPP molecules, the XPS peak of the carbon (C) group in g-C3N4 moves to a higher binding energy, while the C-NH peak position of the g-C3N4 end group remains unchanged. 3 Hybridized nitrogen (N-(C)3) and sp 2 The peak of the hybridized carbon-nitrogen (CN=C) group also moves to a higher binding energy. These changes indicate that the electron density in g-C3N4 decreases after the composite. At the same time, the oxygen (O1s) peak of TCPP in the CN-TCPP-Cu material moves to a lower binding energy compared to the single TCPP molecule, which indicates that after TCPP combines with g-C3N4, the O1s electron cloud density of TCPP increases, which means that electrons are transferred from g-C3N4 to TCPP through the carboxyl oxygen (O).

[0113] In summary, in CN-TCPP-Cu, the electron density of TCPP increases, while the electron density of C, N, and Cu decreases. The inventors of the present invention speculate that in the photocatalytic reaction, the photogenerated electrons continuously transfer from the C3N4 conduction band CB of g-C3N4 to the lowest unoccupied molecular orbital (LUMO) of TCPP through the Cu bridge, constructing a typical Z-type heterostructure, which can effectively inhibit the recombination of electrons and holes, thereby facilitating the improvement of photocatalytic efficiency.

[0114] 2. Antibacterial performance test

[0115] 2.1 Experimental methods

[0116] Escherichia coli (E. coli) was used as the experimental strain, and the antibacterial activity of the material was evaluated by the plate coating method. The E. coli strain was activated in LB liquid medium and incubated at 37°C for 12 h. Then, a bacterial suspension was prepared in a NaCl solution (0.9 wt%) and the bacterial density was diluted to 1×10 8 cfu / mL, corresponding to OD670 =0.03. Then, 1 mL of bacterial solution was mixed with 1 mL of 500 μg / mL suspension of CN-TCPP-Cu and its comparative samples CN-Cu, CN-TCPP / Cu, and CN-TCPP, dispersed in a transparent glass bottle, and diluted with 3 mL of NaCl solution (0.9 wt%) (the bacterial density after dilution was 2 × 10 7 cfu / mL, the concentration of antibacterial material was 100μg / mL), and two groups of mixed solutions were prepared with the same material, divided into experimental group and control group. Then the experimental group was placed under a 300W Xe lamp (with a UV cutoff filter of λ<420nm, and a light power density of 100mW / cm 2 ), irradiate and stir, take 10 μL of samples at different time points, dilute 100 times with NaCl solution (0.9wt%), and then take 100 μL of the diluted E. coli suspension and spread it on a sterile LB agar plate, incubate overnight at 37°C to obtain visible colonies. The control group was stirred in the dark, and the same sampling, dilution, coating and incubation conditions as the experimental group were used. Finally, the colonies on the plate were photographed and recorded.

[0117] 2.2 Antibacterial test results

[0118] The antibacterial test results of CN-TCPP-Cu and CN-Cu under visible light conditions are shown in Figure 5 .Depend on Figure 5 It can be seen that CN-TCPP-Cu exhibits excellent antibacterial properties under light conditions, achieving 100% inhibition rate within 20 min, while CN-Cu requires 50 min to achieve the same effect.

[0119] The antibacterial test results of CN-TCPP-Cu and CN-Cu under dark conditions are shown in Figure 6 .Depend on Figure 6 It can be seen that in the absence of light, neither material showed significant antibacterial effect within 1 hour, which indicates that light is essential for improving the antibacterial properties of CN-TCPP-Cu and CN-Cu. However, after 3 hours, even in the dark, the two materials began to show antibacterial effects, suggesting that the materials themselves may have certain dark toxicity. This dark toxicity may come from the antibacterial properties of the Cu nanoparticles themselves, or from the partially oxidized Cu 2+ The ions are free in the system, thus exerting an antibacterial effect.

[0120] The antibacterial test results of CN-TCPP / Cu and CN-TCPP under visible light and dark conditions are shown in Figure 7 .Depend on Figure 7It can be seen that for CN-TCPP / Cu and CN-TCPP, which are mainly bound by π-π interactions, they failed to show antibacterial effects within 2 hours, whether under light or dark conditions. The present invention believes that this discovery further confirms the importance of the special bridging pillar connection mode between g-C3N4 and TCPP for improving the overall photocatalytic effect of the material. This connection mode not only enhances the light absorption capacity of the material, but also promotes the separation and transmission of photogenerated carriers, thereby achieving more efficient antibacterial performance under light conditions. Therefore, the CN-TCPP-Cu material with a specific composition and structure of the present invention significantly improves the photocatalytic antibacterial performance, and provides important guidance for the development of new and efficient antibacterial materials.

[0121] Figures 5 to 7 Vis refers to visible light conditions, and Dark refers to dark conditions.

[0122] 3. Fluorescence spectroscopy further detects the ability of CN-TCPP-Cu materials to produce reactive oxygen species (ROS) under light conditions

[0123] 3.1 Experimental methods

[0124] 2',7'-dichlorofluorescein was used as a probe for the determination of ROS produced by CN-TCPP-Cu materials. First, 5 mL of a dispersion of CN-TCPP-Cu material with a concentration of 100 μg / mL was prepared in a transparent glass bottle, and then 200 μL of a 10 μmol / L 2',7'-dichlorofluorescein solution was added thereto. The blank control was 200 μL of a 10 μmol / L 2',7'-dichlorofluorescein solution added to 5 mL of ultrapure water. Then, the reaction system and the blank control were placed under a 300 W Xe lamp (equipped with a UV cutoff filter of λ<420 nm, and a light power density of 100 mW / cm 2 ) was irradiated with light while slowly stirring, and the absorption spectrum was detected at an excitation wavelength of 488 nm and an emission wavelength of 524 nm after irradiation for 20 min, 50 min, and 60 min, respectively.

[0125] 3.2 Experimental Results

[0126] See Figure 8 (include Figure 8 Figures a, b, and c in the figure). Reduced 2',7'-dichlorofluorescein can be converted into 2',7'-dichlorofluorescein with high fluorescence quantum yield under the action of ROS, and its fluorescence emission peak is located at 524nm. Figure 8From the data in Figures b and c, we found that there was no significant difference in fluorescence intensity between the blank group (Control) and the experimental group at the beginning of the experiment. However, as the illumination time increased (as shown in Figure a), the fluorescence intensity decayed. This phenomenon indicates that the generation of reactive oxygen species reached a peak within the first 20 minutes of the reaction. The decayed fluorescence signal indicates that at the beginning of illumination, the CN-TCPP-Cu material rapidly catalyzed the generation of a large amount of ROS, which then reacted with 2',7'-dichlorofluorescein, resulting in an enhancement of the fluorescence signal. Over time, the generation rate of ROS may decrease due to saturation of the material surface or recombination of photogenerated carriers, resulting in the decay of the fluorescence signal. These findings further confirm that the CN-TCPP-Cu material has efficient photocatalytic activity under illumination conditions and can produce high levels of ROS in a short time, which is closely related to its excellent antibacterial properties.

[0127] 4. Biocompatibility Assessment

[0128] 4.1 Experimental methods

[0129] 4.1.1 Hemolytic activity assay

[0130] After 1mL of fresh sheep blood was centrifuged at 7100rpm and 4℃ for 5min, the upper serum was discarded, the lower red blood cells were retained, and the red blood cells were washed 4 times with PBS buffer. Then 25mL of PBS buffer was added to obtain a 4% red blood cell solution. 0.2mg of CN-TCPP-Cu material was ultrasonically dispersed in 1mL of PBS buffer to obtain a 200μg / mL CN-TCPP-Cu PBS dispersion, and then 0.5mL of the above dispersion was taken and a 100μg / mL dispersion was obtained by double dilution, and then diluted in the same way to obtain a 50μg / mL dispersion. 100μL of the above dispersions of different concentrations were placed in each well of a 96-well plate, and 100μL of 4% red blood cell solution was added to each well. 200 μL of PBS solution was set as a blank control, and 100 μL of 0.1% polyethylene glycol octylphenyl ether was added to 100 μL of 4% red blood cell solution as a positive control. The experimental group and the control group were made in triplicate. Finally, the 96-well plate was sealed and incubated at 37°C for 4 hours, and the OD was measured by an enzyme-labeled instrument. 540 The hemolysis rate was calculated by the formula: hemolysis rate (%) = (A-A0 / A t -A0)×100%.

[0131] Where A is the absorption rate of the red blood cell supernatant with CN-TCPP-Cu material added, A0 is the absorption rate of the PBS solution, and A t It is the absorbance of the solution after complete hemolysis of the positive control.

[0132] 4.1.2 Cytotoxicity test

[0133] MTT reagent was used to detect the cytotoxicity of antibacterial materials. First, Hela cells were inoculated in DMEM culture medium containing 10% fetal bovine serum and 1% double antibody, and cultured in a humidified environment at 37°C and 5% CO2. After the cell proliferation reached 70-80% density, the cells were digested and blown down with 0.25% trypsin, centrifuged and washed twice with DMEM culture medium, and the cells were diluted to 10 3 -10 4 The cells were inoculated into a 96-well plate at a concentration of 10 cells / mL and cultured for 24 hours to allow them to adhere to the wells. Gently aspirate the culture medium, then add 100 μL of the DMEM dispersion of CN-TCPP-Cu that had been ultrasonically dispersed and graded diluted in advance. The negative control was to add 100 μL of DMEM culture medium, and the blank control was to add only DMEM culture medium to the blank wells. After 24 hours of culture, 100 μL of culture medium containing 10 μL of MTT (0.5 mg / mL, PBS) was added to each well. After 4 hours of culture, the solution was carefully aspirated from the wells, and 150 μL of DMSO solution was added to each well to dissolve the formed formazan crystals. The 96-well plate was placed in a shaker at 37°C and 120 rpm for 10 minutes, and then analyzed using an enzyme reader (λ=570 nm). The formula for calculating cell activity is: Cell activity (%)=[(B-B0)-(B t -B0)] / (B-B0)×100%.

[0134] Among them, B is the absorbance of the negative control, B0 is the absorbance of the blank control, and B t is the absorbance of the experimental group.

[0135] 4.2 Experimental Results

[0136] The experimental results are shown in Figure 9(a) and Figure 9(b).

[0137] The results of the hemolysis test are shown in Figure 9(a). The hemolysis test is a key indicator. The hemolysis test measures the degree to which red blood cells rupture and release hemoglobin after the material comes into contact with red blood cells. High hemolysis usually indicates that the material may be biologically toxic. The experimental results show that at concentrations of 50, 100, and 200 μg / mL, the composite photocatalytic material CN-TCPP-Cu of the present invention did not cause obvious hemolysis, which indicates that at these concentrations, the material is very destructive to red blood cells and has good biocompatibility, providing safety guarantees for the application of composite photocatalytic materials in the biomedical field.

[0138] In FIG. 9( a ), TritionX-100 refers to polyethylene glycol octylphenyl ether cell permeabilization agent, and PBS refers to pure PBS buffer.

[0139] The results of the cytotoxicity test on Hela cells are shown in Figure 9(b). The results also confirm the safety of the CN-TCPP-Cu of the present invention. In the range of experimental concentration ≤100μg / mL, the material exhibited low cytotoxicity and the cell survival rate exceeded 85%. Even at higher concentrations, the cell survival rate remained above 80%, further confirming the low toxicity characteristics of CN-TCPP-Cu. The present invention believes that these findings are extremely important for evaluating the clinical application potential of CN-TCPP-Cu as an antibacterial material, because low hemolysis and low cytotoxicity mean that the material has a low potential risk of damaging healthy human cells in practical applications.

[0140] The present invention is not limited to the above-mentioned embodiments. Without departing from the essential content of the present invention, any deformation, improvement and substitution that can be conceived by those skilled in the art shall fall within the scope of the present invention.

Claims

1. A method for preparing a g-C3N4-porphyrin composite photocatalytic material, characterized in that: The following steps are involved: 1) Providing an aqueous dispersion of nano-scale g-C3N4; 2) mixing an aqueous dispersion of nano-scale g-C3N4 with an aqueous solution of a copper salt to obtain a mixture; reacting the mixture under light with a wavelength λ greater than or equal to 420 nm, and separating the solid and the liquid after the reaction to obtain an intermediate product; 3) dispersing the intermediate product in alcohol to obtain an alcohol dispersion of the intermediate product; heating the alcohol dispersion of the intermediate product and an alcohol solution of porphyrin to react to obtain a g-C3N4-porphyrin composite photocatalytic material.

2. The preparation method according to claim 1, characterized in that: In step 1), the concentration of the aqueous dispersion of nano-sized g-C3N4 is 0.5-5 mg / mL.

3. The preparation method according to claim 1, characterized in that: In step 2), the concentration of the copper salt aqueous solution is 4 to 20 mmol / L, and the copper salt in the copper salt aqueous solution is selected from one of copper chloride, copper sulfate, copper nitrate and copper acetate; In step 2), the nano-g-C3N4 in the aqueous dispersion of nano-g-C3N4 and the Cu in the copper salt aqueous solution 2+ The dosage ratio is 25mg:0.03~0.1mmol.

4. The preparation method according to claim 1, characterized in that: In step 2), a water dispersion of nano-scale g-C3N4 is mixed with a copper salt aqueous solution, and air in the system is removed to obtain a mixture; the mixture is reacted under the light of a 300-400W Xe lamp, and a UV cutoff filter is installed on the Xe lamp to intercept light with a wavelength λ less than 420nm; In step 2), the solid obtained by solid-liquid separation is washed and dried to obtain an intermediate product.

5. The preparation method according to claim 1, characterized in that: In step 3), the concentration of the alcohol dispersion of the intermediate product is 0.3-5 mg / mL; the concentration of the alcohol solution of the porphyrin is 0.03-5 mmol / L; the volume ratio of the alcohol dispersion of the intermediate product to the alcohol solution of the porphyrin is 1-2:1; the alcohol is selected from at least one of methanol, ethanol and isopropanol.

6. The preparation method according to claim 1, characterized in that: In step 3), the alcohol dispersion of the intermediate product and the alcohol solution of porphyrin are reacted under reflux conditions for 6 to 18 hours; after the reaction is completed, the solvent is removed and dried to obtain a g-C3N4-porphyrin composite photocatalytic material; In step 3), the porphyrin is tetrakis(4-carboxyphenyl)porphine.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The nanoscale g-C3N4 is prepared by the following steps: (a) calcining urea or melamine, grinding, and obtaining a grinding product; (b) dispersing the ground product in water and subjecting it to ultrasonic treatment to obtain a mixed solution; (c) The mixed solution is centrifuged at a speed of 2500-4500 rpm to obtain an upper dispersion; the upper dispersion is then centrifuged again at a speed of 7000-12000 rpm, the precipitate is dried to obtain nano-scale g-C3N4.

8. The preparation method according to claim 7, characterized in that: The calcination temperature is 500-700°C, and the calcination time is 1.5-4h.

9. A g-C3N4-porphyrin composite photocatalytic material, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the g-C3N4-porphyrin composite photocatalytic material according to claim 9 in the preparation of photocatalytic antibacterial materials.

Citation Information

Patent Citations

  • Au / g-C3N4 all-weather photocatalytic antibacterial material and bright-dark dual-mode antibacterial mechanism thereof

    CN112375804A

  • High-valence silver, zinc and copper composite nano antibacterial agent and preparation method thereof

    CN113383792A

  • Novel g-C3N4 / ZnO composite photocatalytic material as well as preparation method and application thereof

    CN116809108A

  • Photocatalytic nano-composite coating as well as preparation method and application thereof

    CN117779152A

  • Porphyrin self-assembly material as well as preparation method and application thereof

    CN118652258A